2006
DOI: 10.1016/j.jpain.2006.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Chronic Pain Following Breast Cancer Surgery: A Prospective Study

Abstract: Clinical variables and severe acute pain were risk factors for chronic pain following breast cancer surgery, but psychosocial distress was not, which provides a basis for hypothesizing that aggressive management of acute postoperative pain may reduce chronic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
355
13
17

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 460 publications
(410 citation statements)
references
References 59 publications
25
355
13
17
Order By: Relevance
“…Factors such as age [9,22], female gender 1221, and opioid consumption have been identified as predictors of the transition to CPSP [4]. Our results failed to demonstrate such associations (Table 1).…”
Section: Introductioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Factors such as age [9,22], female gender 1221, and opioid consumption have been identified as predictors of the transition to CPSP [4]. Our results failed to demonstrate such associations (Table 1).…”
Section: Introductioncontrasting
confidence: 75%
“…Studies have reported that female gender [9] and younger age [9,40) predicted intense acute postoperative pain, and nationwide surveys consistently find that the incidence of chronic neuropathic pain is significantly higher in women than men [4143]. Several smaller studies of CPSP have also identified younger age as a risk factor for the transition from acute pain to pain chronicity [14,22]. The sample of patients enrolled in the present study was quite homogeneous with respect to age and gender and neither predicted chronic pain 6 months after total hip arthroplasty [19].…”
Section: Introductionmentioning
confidence: 99%
“…For example, chronic pain in breast cancer survivors is related to more invasive surgery, multiple treatments such as surgery combined with radiation, and post-operative pain (Poleshuck EL 2006). Treatment for head and neck cancers, the sixth most prevalent cancer globally, commonly leads to disfigurement, chronic pain and poor functional outcomes (Chin 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Effective postoperative analgesia is of major importance for preventing POCP. 6,7 Gabapentin is known to reduce dorsal horn neuron excitability and central sensitization through various mechanisms. [8][9][10] A review of the literature suggested that the incidence of postoperative chronic pain was reduced through using gabapentin perioperatively.…”
Section: Introductionmentioning
confidence: 99%